The Inhibitory Effect of Aqueous Extract of Coriander (Coriandrum sativum L.) Leaves on the Activity of Male Reproductive System of Albino Mice - Al-Rubaye, Rana Hanan Khudhair (Iraqi Journal of Science, 2023)
The aim of present study to investigate the effect of Coraindrum sativum leaves extract on reproductive activity of male albino mice .Thirty male mice with age of 80-100 day and weight between 25-30 g were divided into three groups: group 1 (untreated), group 2 and 3 were administrated orally for 30 days with aqueous extract of Coraindrum sativum leaves at dose 125 and 250mg/kg.b.w. respectively.The following parameters were evaluated: serum testosterone levels, testes weights, sperm characteristics [motility, viability, spermatozoa, morphology and concentration] and histology changes of the testis. The results showed that the treatment caused highly significant degrease (P<0.01) in testosterone levels and the weight of testes associated with highly significant decrease (P<0.01) in sperm progressive motility, viability and concentration while the percentage of abnormal sperms was increased significantly. Testicular histology showed gradual degeneration in the population of germ cells lining seminiferous tubules and also degeneration in the interstitial tissue of Leydig cells.In conclusion, the results indicate that Coraindrum sativum leaves extract at dose 125 and 250 mg/kg.b.w. has antifertility effect in male albino mice.